Blended learning in vocational education: benefits, challenges, and student engagement - Su Song; Yiu Chi Lai (Cogent Education)
This systematic review aims to explore blended learning in vocational education (VE), where the benefits, challenges, and influence on student engagement will provide information on some recommendations that can be adopted to better design and implement. The need for this review arises from the global emphasis on technology-driven and flexible vocational training, given the rapid changes in learner needs and industry demands. The existing literature needs a comprehensive view of the way learning influences engagement in VE contexts. The review is an analysis of 24 articles selected via a systematic process guided by the PRSIMA framework that provides insights on key trends and gaps. Results show that blended learning requires a flexible approach to student engagement, where it works out solutions for pedagogical, technological, and learner-centered barriers. It indicates that the use of technology, such as gamification, needs to deal with ambiguity. Learner satisfaction and motivation are linked to their engagement levels. Financial, training and technical support are crucial for aiding student engagement in blended learning. Implications for policy, practice, and future research are extracted from findings to initiate a cohesive outlook on blended learning in VE and to optimize student engagement.